Development of PLEAD: A Database Containing Event‐based Runoff Phosphorus Loadings from Agricultural Fields. Issue 2 (1st March 2019) - Bolster, Carl H.; Baffaut, Claire; Nelson, Nathan O.; Osmond, Deanna L.; Cabrera, Miguel L.; Ramirez‐Avila, John J.; Sharpley, Andrew N.; Veith, Tamie L.; McFarland, Anne M. S.; Senaviratne, Anomaa G. M. M. M.; Pierzynski, Gary M.; Udawatta, Ranjith P.
Abstract : Computer models are commonly used for predicting risks of runoff P loss from agricultural fields by enabling simulation of various management practices and climatic scenarios. For P loss models to be useful tools, however, they must accurately predict P loss for a wide range of climatic, physiographic, and land management conditions. A complicating factor in developing and evaluating P loss models is the relative scarcity of available measured field data that adequately capture P losses before and after implementing management practices in a variety of physiographic settings. Here, we describe the development of the P Loss in runoff Events from Agricultural fields Database (PLEAD)—a compilation of event‐based, field‐scale dissolved and/or total P loss runoff loadings from agricultural fields collected at various research sites located in the US Heartland and southern United States. The database also includes runoff and erosion rates; soil‐test P; tillage practices; planting and harvesting rates and practices; fertilizer application rate, method, and timing; manure application rate, method, and timing; and livestock grazing density and timing. In total, >1800 individual runoff events—ranging in duration from 0.4 to 97 h—have been included in the database. Event runoff P losses ranged from <0.05 to 1.3 and 3.0 kg P ha −1 for dissolved and total P, respectively. The data contained in this database have been used in multiple research studies to address important modeling questions relevant to P management planning. We provide these data to encourage additional studies by other researchers. The PLEAD database is available at https://doi.org/10.15482/USDA.ADC/1482380 . Core Ideas: Development of database containing P loss from agricultural fields is described. We provide public access to P loss data for individual runoff events. The data can be used to evaluate P loss models and P Indices.